2013
DOI: 10.1002/mnfr.201300417
|View full text |Cite
|
Sign up to set email alerts
|

Plant polyphenol induced cell death in human cancer cells involves mobilization of intracellular copper ions and reactive oxygen species generation: A mechanism for cancer chemopreventive action

Abstract: Scope: Anticancer polyphenolic nutraceuticals from fruits, vegetables, and spices are generally recognized as antioxidants, but can be prooxidants in the presence of copper ions. We earlier proposed a mechanism for such activity of polyphenols and now we provide data in multiple cancer cell lines in support of our hypothesis. Methods and results: Through multiple assays, we show that polyphenols luteolin, apigenin, epigallocatechin-3-gallate, and resveratrol are able to inhibit cell proliferation and induce ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 36 publications
7
73
0
Order By: Relevance
“…In the presence of copper ions, of which there are more in cancer cells than in normal cells (31), at least some polyphenols (luteolin, apigenin, epigallocatechin-3-gallate and resveratrol) act as pro-oxidants. The anti-tumour effect of these polyphenols decreases significantly in the presence of copper chelators (32).…”
Section: A Spleenmentioning
confidence: 99%
“…In the presence of copper ions, of which there are more in cancer cells than in normal cells (31), at least some polyphenols (luteolin, apigenin, epigallocatechin-3-gallate and resveratrol) act as pro-oxidants. The anti-tumour effect of these polyphenols decreases significantly in the presence of copper chelators (32).…”
Section: A Spleenmentioning
confidence: 99%
“…Recently, Khan et al (2014) proposed that the fact that carcinogenic cells have higher levels of copper compared with non-malignant cells and may be more susceptible to the transfer of electrons with antioxidants to generate ROS, so damage to DNA by copper may be an important route by which carcinogenic cells can die in the presence of polyphenols, while normal cells can survive (Azmi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MPO activity is high in HL-60 cells [37] . Khan et al [38] found that the use of neocuproine, a chelator of Cu 2+ ions, inhibits polyphenol-induced apoptosis in cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%